(untitled) (Zaporizhzhia Historical Review, 2021)
The actual linguo-culturological problem is analyzed – literary-aesthetical value of artistic translation as an important factor of the Ukrainian literary language functioning and specificity of the secondary text, raised on the basis of the conditions of inter-cultural communication.